1985
DOI: 10.1016/0033-5894(85)90086-9
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of High Sea Level during Isotope Stage 5c in Queensland, Australia

Abstract: Thirty-nine species of scleractinian corals have been recovered from under a high dune on the western (mainland) side of North Stradbroke Island, eastern Australia. The corals are associated with thin intertidal sediments and their good condition implies burial in situ and preservation in a saturated zone. Most likely this occurred as the coast prograded and a large dune advanced into the littoral zone, burying intertidal sediments and coral. The species assemblage indicates a sheltered environment but one ope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…The apparent continuation of dune sands to present sea-level in southern Queensland and the overlap there of stranded foredunes (Ward & Grimes 1987), marine sediments (Pye 1983) and corals (Kelley & Baker 1984;Pickett et al 1984Pickett et al , 1985 prove that dune-building extended into interglacial and postglacial time, but the relations to coastal strandplains show that major dunebuilding then stopped-shortly after 6700 14 C years BP for the postglacial (Ward & Grimes 1987). The causes of the sand movement had evidently ceased to operate, and vegetation reclaimed the moving sands.…”
Section: Relation To Glacial and Interglacial Agesmentioning
confidence: 96%
See 1 more Smart Citation
“…The apparent continuation of dune sands to present sea-level in southern Queensland and the overlap there of stranded foredunes (Ward & Grimes 1987), marine sediments (Pye 1983) and corals (Kelley & Baker 1984;Pickett et al 1984Pickett et al , 1985 prove that dune-building extended into interglacial and postglacial time, but the relations to coastal strandplains show that major dunebuilding then stopped-shortly after 6700 14 C years BP for the postglacial (Ward & Grimes 1987). The causes of the sand movement had evidently ceased to operate, and vegetation reclaimed the moving sands.…”
Section: Relation To Glacial and Interglacial Agesmentioning
confidence: 96%
“…However, this explanation is inadequate as the loss of the native cover in fires today has not resulted in renewed wind erosion. Pickett et al (1985) reported 230 Th/ 234 U dates on corals recovered by a dredge working in a pond among dunes close to the western shore of North Stradbroke Island. The dates allowed them to correlate the corals with MIS (marine isotope stage) 5c and suggested that the sea at this time was higher than previously recognised.…”
Section: Relation To Glacial and Interglacial Agesmentioning
confidence: 98%
“…Deep sea cores provide material for oxygen isotope analysis, which can be generally related to global warming or cooling (Emiliani 1961(Emiliani , 1972Chappell 1974b;Shackleton 1982). Along tectonically stable coastlines Quaternary sea-levels are recorded as discontinuous shoreline deposits (Marshall & Thom 1976;Veeh et al 1979;Pickett et al 1985;Semeniuk 1985;Ward 1985). Fades interpretation of continental shelf and marginal marine sediment has led to meaningful correlations with other established data (Hails et al 1984a,b;Blom 1988).…”
Section: Introductionmentioning
confidence: 93%
“…The dune systems demonstrate considerable antiquity, with the Kabali area of the Cooloola sandmass dated to approximately 730kya (Tejan-Kella et al 1990), the central dune system of Fraser Island to ~600kya (Longmore 1997), and the dune systems of North Stradbroke Island to ~120kya (Neil 1998;Pickett et al 1984Pickett et al , 1985. Bribie Island demonstrates low Pleistocene beach accretion ridges .…”
Section: Sea-level Change and Geomorphologymentioning
confidence: 99%
“…In 2011 Moss et al also reported on the palaeoecology of Myora Springs over the past 800 years. Other palaeoecological studies include those by Barr et al (2013) at Blue Lake, Boyd (1993) on the pollen record of the 600 year old Eighteen Mile Swamp, and Pickett et al (1984) and Pickett et al (1985) on fossil corals buried beneath the dunes at Amity…”
Section: North Stradbroke Islandmentioning
confidence: 99%